2002
DOI: 10.1136/vr.150.7.205
|View full text |Cite
|
Sign up to set email alerts
|

Straelensiosis in dogs: a newly described nodular dermatitis induced by Straelensia cynotis

Abstract: A distinctive nodular dermatitis induced by Straelensia cynotis, a newly described trombidioid larval mite which resides in hair follicles, was identified in 12 dogs living in France. They all had scattered, small (1 to 3 mm in diameter), pale, firm skin nodules, variable in distribution but always affecting the dorsal regions of the head and trunk; they were distributed over the whole body of seven of the dogs. The animals were otherwise healthy except for three severely infested fox terriers which had a decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
32
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 5 publications
8
32
1
Order By: Relevance
“…The present 12 cases, diagnosed in Israel, occurred mostly in mountainous areas in Israel, in which ambient temperatures are cooler. All affected pets were free to roam the environment, in agreement with previous reports, which documented straelensiosis in rural and hunting dogs (Le Net et al 2002, Ramirez et al 2009).…”
Section: Straelensiosis In Cats and Dogs In Israelsupporting
confidence: 91%
See 4 more Smart Citations
“…The present 12 cases, diagnosed in Israel, occurred mostly in mountainous areas in Israel, in which ambient temperatures are cooler. All affected pets were free to roam the environment, in agreement with previous reports, which documented straelensiosis in rural and hunting dogs (Le Net et al 2002, Ramirez et al 2009).…”
Section: Straelensiosis In Cats and Dogs In Israelsupporting
confidence: 91%
“…The high frequency of marked pruritus in the present cases is interesting, and was often the chief complaint at presentation, in contrast to several previous reports (Le Net et al 2002, Degorce-Rubiales et al 2008, Ramirez et al 2009). These concluded that (Ramirez et al 2009).…”
Section: Straelensiosis In Cats and Dogs In Israelcontrasting
confidence: 70%
See 3 more Smart Citations